Studies on periphyton grazing rate of Labeo calbasu (Hamilton) - Rahman, M M; Haque, M M; Narejo, N T; Islam, S; Rahmatullah, S M (Indian Journal of Fisheries, 2011)
Studies were undertaken to investigate the grazing rate of Labeo calbasu on periphyton for a period of ten months from July 1998 to April 1999. It was observed that periphyton density significantly (p<0.05) influenced the grazing rate of L. calbasu. The lowest (0.0039 dmg/fish/4h)and highest (0.1037mg/fish/4h) grazing rates in the same size group of fish were found at 1 slide/aquarium (100 cm2) and 4 slides/aquarium (400 cm2) respectively. Similarly, size group of fish significantly (p<0.05) influenced the grazing rate. The lowest (0.0030 dmg/fish/4h) and the highest (0.0826 dmg/fish/4h) grazing rates were observed in smaller size and larger size group of fish respectively. However, significantly (p<0.05) high grazing rate (0.155 dmg/fish/4h) was observed in group than individual fish (0.060 dmg/fish/4h). The grazing rate was also significantly (p<0.05) influenced by time duration